An Analytical View of Nonlinear Fractional Burger’s Equations Using Conformable Double Elzaki Transform - Eltaib M. Abd Elmohmoud; Mohamed Z. Mohamed; M. Magzoub; Alla Mahmoud Elsheikh (Journal of Function Spaces)
The conformable double Elzaki composition technique (CDET) and the Adomian decomposition technique are combined in this work to provide a novel approach for dealing with nonlinear partial issues under certain specified conditions. The conformable double Elzaki composition (CDEC) approach is the name we give to this novel technique. We also outline and discuss the main traits and major conclusions connected to the recommended technique. The new technique provides an estimated succession of answers that finally get close to the exact solution. This method has the advantage of generating findings rapidly since it generates analytical series solutions for the target equations without the requirement for discretization, transformation, or limited assumptions. We also present some numerical applications to back up our conclusions. The results demonstrate the strength and potency of the recommended strategy in dealing with a variety of problems in the fields of engineering and physics in symmetry with other strategies.